Timescale competition dictates thermo-mechanical responses of NiTi shape memory alloy bars. (1st June 2020) - Zhuo, Mingzhao
Highlights: A dimensionless number λ expressing the timescale ratio of the loading time to the characteristic time of heat transfer is defined for shape memory alloys under force- or displacement-controlled cyclic loadings. The timescale ratio reflects the resultant effect of the loading rate, ambient conditions, and the specimen geometry. The coupled model performs well in predicting the thermo-mechanical responses and the stress strain hysteresis when compared with experimental data. Abstract: NiTi shape memory alloys (SMAs) exhibit distinct thermo-mechanical behaviors affected by the loading frequency, ambient conditions, and the specimen geometry. The effects of these factors are essentially due to the competition of different timescales in phase transitions of NiTi SMAs. However, quantifying the timescale competition still remains a challenge for SMAs subjected to force- or displacement-controlled cyclic loadings. Here we present a thermo-mechanically coupled model for one-dimensional SMA bars to address the effects of timescale competition on the thermo-mechanical responses. Scaling the model gives a dimensionless number λ indicating the ratio of the loading time to the characteristic time of heat transfer (affected by ambient conditions and the specimen geometry). The model shows that it is the timescale ratio λ that dictates the thermo-mechanical responses. Comparison of simulation results with experimental data validates the coupled model and the effects of the timescale ratio λ on the thermo-mechanical responses. The coupled model can predict the responses of SMAs under different combinations of external loadings and ambient conditions and thus provide guidelines for experimental design.